Quantification of conversion and degradation of circulating angiotensin in rats - Bauer, Johannes; Berthold, Heike; Schaefer, Franz; Ehmke, Heimo; Parekh, Niranjan (American journal of physiology. Regulatory, integrative and comparative physiology, 1999)
The aim of the present study was to quantify with a uniform technique the rates of conversion of ANG I to ANG II in the lung and kidney and the degradation of both peptides to biologically inactive products in the pulmonary, renal, and systemic circulation. We infused the peptides intravenously, into the left ventricle, and into the left renal artery of rats and compared their effects on renal blood flow.
Gesehen am 10.12.2020